Pengaruh Keuangan Daerah dan Suku Bunga terhadap Investasi dan PDRB di Jawa Tengah Tahun 2018-2022 - Audiana, Misna; Aji Suseno , Deky (Jurnal Bingkai Ekonomi (JBE), 2024)
This research aims to analyze the influence of regional tax revenues on GRDP, the influence of Regional Financial Transfers (TKD) on GRDP, the influence of regional tax revenues on investment, the influence of interest rates on investment, the influence of government spending on investment. . , the influence of Regional Financial Transfers (TKD) on investment, and the influence of investment on Gross Regional Domestic Product (GRDP). The data in this study uses secondary data obtained from data on regional tax revenues, interest rates, government expenditure, regional financial transfers, capital investment (PMA and PMDN) and Gross Regional Domestic Product (GRDP) on the basis of constant prices for each district. /city in the Center. . Java Province 2018 - 2022. The results of the research show that regional tax revenues have a significant positive effect on GRDP, Regional Financial Transfers (TKD) have a significant positive effect on Gross Regional Product (GRDP), regional tax revenues have a significant positive effect on investment, interest rates have a negative effect significant on investment, government spending has a significant positive effect on investment, Regional Financial Transfer (TKD) has a positive and insignificant effect on investment, investment has a significant positive effect on GRDP. Keywords: Investment, GRDP, Regional Financial Revenues, Government Expenditures, Interest Rates.